Tourism as a Soft Power Tool. The Role of Public Diplomacy in Japan’s Country and Destination Branding - Casado Claro, María-Francisca; Pastrana Huguet, Josep; Saavedra Serrano, María Concepción (Journal of Tourism, Sustainability and Well-being, 2023)
Tourism plays an important part in soft power as a public diplomacy tool that, alongside destination branding, aims to reinforce the image of a place to attract visitors, with the ensuing multiplier effect on its economy. Both destination branding and public diplomacy seek the common goal of generating a positive reputation and image of the place, although they pursue different interests. On the one hand, destination branding aims at attracting tourists with an eminently economic objective in mind; while, on the other hand, public diplomacy seeks to promote national interests (economic, social, political), and advance foreign policy goals. Destination branding and public diplomacy can be regarded as two faces of the same coin, as together they leverage a country’s equity in soft power. Japan has furthered its economic, social, and political goals by projecting the image of a technologically advanced country boasting a rich cultural tradition through skillful management of its soft power and its public diplomacy, that in recent times has revolved around cultural diplomacy with the “Cool Japan” strategy for the promotion of cultural industries, as well as around sports diplomacy, with the celebration of the Tokyo 2020 Olympic Games, which owing to the COVID pandemic became an example of failed destination branding, that nevertheless did not obscure their success in terms of sports diplomacy.